Effect of subclinical mastitis on milk yield and milk composition parameters in dairy camels - Hadef, Leyla; Hamad, Brahim; Aggad, Hebib (Acta Biologica Szegediensis, 2020)
This study investigated the effects of subclinical mastitis on milk yield and milk composition parameters in dairy camels. A total of 140 camel milk samples were collected from multiparous she-camels (7-10 years old) and were subjected to bacteriological culture studies; 76 samples displayed subclinical mastitis and 64 samples were healthy. Furthermore, the samples were analyzed via standard procedures to determine the yield and composition parameters of the milk such as pH, electrical conductivity, protein, fat, lactose, and ash content. The results showed that the milk yield was significantly low (p < 0.05) in infected animals compared to healthy animals (3.80 vs 4.32 L·day-1). Moreover, compared to the values observed in healthy milk samples, milk from animals with subclinical mastitis showed significantly decreased (p < 0.05) protein (3.33 vs 3.40%) and fat (3.67 vs 3.74%) contents. However, no significant changes (p > 0.05) were observed in pH, electrical conductivity, lactose, or ash content. The results of the uninfected milk samples revealed that there was significant correlation between the protein and fat content (r = 0.781; p < 0.01) and between the lactose and ash content (r = 0.701; p < 0.01). Conversely, the infected ones showed that there was higher significant correlation between the protein and fat contents (r = 0.807; p < 0.01) and a medium correlation between the lactose and ash contents (r = 0.603; p < 0.01). In conclusion, the results suggest that subclinical mastitis is negatively associated with a reduced milk yield and lower protein and fat content. Thus, these parameters can be used to diagnose mastitis in dairy camels.